Rationale of the evaluation and selection of kinematic and tribological characteristics of the system «pinion – gear rack» of cold-pilgering mills - Kadilnikova, T. M.; Sushko, L. F. (Science and Transport Progress, 2014)
Purpose. During operation of cold-pilgering mills rotation of the shafts is carried out by means of pinion gears being in meshing with stationary gear racks, which is accompanied by various tribological defects, that can be avoided during the detailed investigation and justification of selection and evaluation of kinematic and tribological characteristics of the system "pinion - gear rack". Methodology. Runout occurs as a consequence of increased friction and depends on the material hardness of which pinions and toothed racks are manufactured, their thermal treatment, selection of correct lubrication, insufficient oil purity and its untimely change, gears overload and other factors. To assess the runout of tribological pair cogs "pinion - gear rack" of the cold-pilgering mills we will use a system of differential equations of the first order. Using the solution of this system under the given conditions, it is possible to obtain relations for kinematic and tribological parameters. Findings. Relations for the durability, runout, sliding speed, and length of the line of the tribological pair "pinion - gear rack" contact are obtained. They provide high indicators of runout and durability of the system with minimum weight and overall dimensions of the design, which is an important factor to increase efficiency of cold-pilgering mills. Originality. The analysis of the relations, which was obtained to identify durability, wear, sliding speed, and the length of the line of the tribological pair "pinion - gear rack" contact allows you to choose for cold-pilgering mills special pinions with the design parameters, which optimally satisfy the technological conditions of rolling. Practical value. Analytical determination of the slip velocity for tribological pair makes it possible to adjust the technical process of cold-pilgering mills and to make constructive changes in the system of "pinion - gear rack" in order to increase its wear resistance.